THE MEASURE OF LAW AS AN EXPRESSION OF THE LEGAL MEANING EMBEDDED IN CUSTOMARY LAW - Kaneva, Svetla Marinova (International Journal of Legal and Social Order, 2025)
Relying on the phenomenologica approach to the Law the measure of law is problematized as an expression of legal meaning, of its qualities of ambivalence, contradiction, polyvariance, justice. Its genesis is in the customary law. Legal measure is an expression of social dependencies, it contains the pattern of law. It reflects the correct and fair distribution of goods, the expression of legal position subjects on the occasion of goods at a certain stage of human development.